Pengaruh Financial Knowledge, Financial Attitude, dan Financial Self-efficacy terhadap Personal Financial Management Behavior Pedagang UMKM di Stadion Gelora Bangkalan - Erfianti, Rani Yulia; Susandini, Aprilina (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine the effect of Financial Knowledge, Financial Attitude, and Financial Self-efficacy on the Personal Financial Management Behavior of MSME Traders at Gelora Bangkalan Stadium. The population used in this study were 187 traders with sampling using purposive sampling method and 127 traders were selected as samples in this study. The method used is descriptive quantitative. The data used in the study were obtained by distributing questionnaires to MSME traders at the Gelora Bangkalan Stadium. The results of this study indicate that financial knowledge has a positive and significant effect on the personal financial management behavior of MSME traders at the Bangkalan Gelora Stadium, financial attitude has a positive and significant effect on the personal financial management behavior of MSME traders at the Bangkalan Gelora Stadium, financial attitude has a positive and significant effect on personal finance management behavior of MSME traders at the Bangkalan Gelora Stadium, and financial knowledge, financial attitude, and financial self-efficacy simultaneously have a positive and significant effect on the personal financial management behavior of MSME traders at the Bangkalan Gelora Stadium